Angiosperms in Narsingdi district of Bangladesh: Class Liliopsida (Bangladesh Journal of Plant Taxonomy, 2020)
This study provides the taxonomic data on 168 plant species belonging to 96 genera and 23 families of Liliopsida (monocotyledons) extant in Narsingdi district of Bangladesh. These species are mostly comprised of herbs (90.48%), followed by trees and shrubs (4.76% each). Poaceae with 66 species under 37 genera is the best represented family, followed by Cyperaceae with 26 species of seven genera, Araceae with 16 species of 11 genera, Commelinaceae with 11 species of four genera and Arecaceae with 10 species of eight genera. Cyperus with 13 species appears as the largest genus, which is followed by Panicum with nine species, Digitaria with six species, and Commelina and Dioscorea with five species each. The six upazilas of this district are 39.77% similar in the species composition of their Liliopsida, but the similarity between the pairs of upazilas varies from 6.45% to 32.31%. Roadside and fallow land habitats share the highest similarity (36.84%) in species composition. Total 117 species are distinguished as economically useful. This study suggests for implementation of necessary measures in order to minimize the major threats to this plant group and to favor its sustainable development in the study area.Bangladesh J. Plant Taxon. 27(2): 391-405, 2020 (December)